Recent Advances in Halophilic Protozoa Research. (6th February 2018) - Harding, Tommy; Simpson, Alastair G. B.
Abstract: Most research on microorganisms adapted to hypersaline habitats has focused on Archaea and Bacteria, with microbial eukaryotes receiving much less attention. Over the past 15 yr, our knowledge of phagotrophic microbial eukaryotes, i.e. protozoa, from hypersaline habitats has greatly improved through combinations of microscopy, molecular phylogenetics, environmental sequencing, transcriptomics and growth experiments. High salinity waters from salterns, other landlocked water masses and deep hypersaline anoxic basins contain unique and diverse halophilic protozoan assemblages. These have the potential to exert substantial grazing pressure on prokaryotes and other eukaryotes. They represent many separate evolutionary lineages; species of Heterolobosea, Bicosoecida, and Ciliophora have been most intensively characterized, with several proven to be extreme (or borderline extreme) halophiles. Transcriptomic examinations of the bicosoecid Halocafeteria (and the heteroloboseid Pharyngomonas ) indicate that high‐salt adaptation is associated with a subtle shift in protein amino acid composition, and involves the differential expression of genes participating in ion homeostasis, signal transduction, stress management, and lipid remodeling. Instances of gene duplication and lateral transfer possibly conferring adaptation have been documented. Indirect evidence suggests that these protozoa use "salt‐out" osmoadaptive strategies.